More than grateful: How employee embeddedness explains the link between psychological contract fulfillment and employee extra-role behavior. (August 2019) - Kiazad, Kohyar; Kraimer, Maria L; Seibert, Scott E
Scholars typically view employee responses to psychological contract (PC) fulfillment as a form of reciprocity; in exchange for the organization fulfilling its promises, the employee willingly contributes their time and effort toward company goals. In this article, we ask if employee responses are based not on gratitude, but rather on the employee's desire to maintain the benefits associated with PC fulfillment. Specifically, we argue that PC fulfillment embeds employees in the organization by increasing the costs of leaving ('sacrifices'), and this in turn motivates their extra-role performance. Furthermore, we expect this effect to be even stronger for employees with strong ties to colleagues or work groups ('links') or good fit with job demands or organizational values ('fit'). Data from 149 employees and their immediate supervisors supported our predictions: PC fulfillment was positively related to organizationally-directed citizenship behaviors and work-role innovation through its positive relation to sacrifices. Furthermore, these indirect effects were stronger for employees with stronger links and better fit. The present findings provide a novel theoretical account of how and when PC fulfillment relates to positive employee behaviors. Theoretical and practical implications for managing employees' PCs are discussed.